Guidelines for the Design of Solid CO2 Adsorbents for Mobile Carbon Capture in Heavy-Duty Vehicles: A Review - Kim, Taenam; Kim, Kangseok; Lee, Giwook; Seo, Minhye; Hwang, Jongkook (Korean Journal of Chemical Engineering, 2024)
The transportation sector is the largest contributor to carbon dioxide (CO2) emissions, largely due to heavy-duty vehicles (HDVs) that inevitably rely on internal combustion engines. Electrification is a promising technology for decarbonizing light-duty vehicles but it is difficult to apply to HDVs with long driving ranges and significant weights. One possible solution is a mobile carbon capture (MCC) system that adapts onboard CO2 capture and storage to the HDV. Although conceptual designs have been presented for MCC systems that use adsorbents and temperature-swing adsorption (TSA), the development of the adsorbent-based MCC remains in its infancy. Since adsorbents play a critical role in determining the overall weight, volume, and energy consumption of the MCC, the development of a high performance adsorbent is a key factor in the successful MCC design. In this review, we aim to provide guidelines for the design of CO2 adsorbents for MCC in HDVs. First, we briefly introduce the adsorbent selection criteria for TSA in MCC, including the CO2 working capacity, purity, stability, and regeneration energy. Then, we summarize recent progress in the development of adsorbents tested under MCC-relevant conditions. Finally, the current challenges and future prospects of MCC are discussed.
Keywords: Adsorptive separation; Capture system; CO2 adsorbent; CO2 capture; Decarbonising; Heavy duty vehicles; Light duty vehicles; Mobile carbon capture; Temperature swing adsorption; Transportation sector; Adsorptive separation; CO2 adsorbent; CO2 capture; Mobile carbon capture